(untitled) (Journal of the College of Basic Education, 2022)
Research SummaryThe dramatic character is one of the basic elements on which the dramatic work is built and based, which transforms according to the changes that occur in the course of events. The research sheds light on the subject of the artistic modalities of character transformation in television drama. The research included four chapters as follows:The first chapter (methodological framework) included the research problem, which was formulated with the following question: (What are the technical modalities for character transformation in TV dramas?).